2016
DOI: 10.1038/srep22084
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Second Primary Cancers in Multiple Myeloma Survivors in German and Swedish Cancer Registries

Abstract: We aimed at investigating the distribution and risk of second primary cancers (SPCs) in multiple myeloma (MM) survivors in Germany and Sweden to provide etiological understanding of SPCs and insight into their incidence rates and recording practices. MM patients diagnosed in 1997–2010 at age ≥15 years were selected from the Swedish (nationwide) and 12 German cancer registries. Standardized incidence ratios (SIRs) were used to assess risk of a specific SPC compared to risk of the same first cancer in the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Prior studies have shown that the incidence of breast, colon, lung, and prostate cancer may be lower among survivors of myeloma compared with the general population . This was hypothetically ascribed to a decrease in cancer screening after diagnosis of a hematologic cancer .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have shown that the incidence of breast, colon, lung, and prostate cancer may be lower among survivors of myeloma compared with the general population . This was hypothetically ascribed to a decrease in cancer screening after diagnosis of a hematologic cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that the incidence of breast, colon, lung, and prostate cancer may be lower among survivors of myeloma compared with the general population. [21][22][23] This was hypothetically ascribed to a decrease in cancer screening after diagnosis of a hematologic cancer. 21,23 Conversely, the nearly 7-fold higher risk of acute leukemia was attributed to the leukemogenic effects of alkylator-based therapy and stem cell transplantation, although the risk of myelodysplasia is notably also increased in patients with monoclonal gammopathy, a premalignant plasma cell dyscrasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Other studies have found MM patients to have an increased risk of developing certain types of second cancers, such as melanoma, nervous system tumors, and kidney and urinary tract tumors, although mechanisms and risk factors are not well understood. [7][8][9][10] Suggested risk factors for second malignancies include treatment-, disease-, environmental-, behavioral-, and host-related factors. 4,[11][12][13] Host-related factors include both genetic and nongenetic; reported nongenetic factors include age, male sex, and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…6 Other studies have found MM patients to have an increased risk of developing certain types of second cancers, such as melanoma, nervous system tumors, and kidney and urinary tract tumors, although mechanisms and risk factors are not well understood. [7][8][9][10] Suggested risk factors for second malignancies include treatment-, disease-, environmental-, behavioral-, and host-related factors. 4,[11][12][13] Host-related factors include both genetic and nongenetic; reported nongenetic factors include age, male sex, and obesity.…”
Section: Introductionmentioning
confidence: 99%